Prevalence of suicidal behavior in children and adolescents of the Krasnodar Territory - E.O. Boyko; Yu.Sh. Vasyanina; Yu.A. Mylnikova; E.K. Aleksanyan (РМЖ. Мать и дитя, 2022)
E.O. Boyko1, Yu.Sh. Vasyanina2, Yu.A. Mylnikova1,2, E.K. Aleksanyan2 1Kuban State Medical University, Krasnodar, Russian Federation 2Specialiazed State Clinical Psychiatric Hospital No. 1, Krasnodar, Russian Federation Background: according to the World Health Organization (WHO), every year about 700,000 people die as a result of suicide. In the age group of 15–19 years, suicide is the fourth leading cause of death. In 2011 UNICEF released the report based on the Federal Service for State Statistics (Rosstat) data, according to which every twelfth teenager aged 13–17 years is trying to commit suicide in Russia. Aim: to study the frequency and case structure of suicidal activity in children and adolescents in the Krasnodar Territory for further improvement of measures to reduce the risk of autoaggressive behavior. Patients and Methods: the article presents the analysis of indicators concerning suicidal activity in children and adolescents of the Krasnodar Territory for the period 2020–2021. The data were obtained from specialists of the psychiatric and pediatric service of the Krasnodar Territory, the Directorate of the Federal Service for State Statistics of the Krasnodar Territory and the Republic of Adygea (Krasnodarstat), and the Directorate for Registry Offices of the Krasnodar Territory with the support of Medical Information and Analytical Center. Results: in 2020, 98 cases of autoaggressive behavior were registered. Of these, 70 (71.4%) cases of incomplete suicide attempts, 25 (25.5%) cases of suicidal statements and 3 (3.1%) completed suicides. In 2021, there were 138 cases of suicidal behavior of minor residents registered in the Krasnodar Territory, of which 91 (65.9%) cases of incomplete suicide attempts, 40 (29%) cases of suicidal statements, intentions and threats without committing a suicide attempt, and 7 (5.1%) cases of completed suicides. In the contingent of persons with incomplete suicidal attempts (90 minors), there was a significant predominance of females 79 (85.9%) and 75 (83.3%) people in 2020 and 2021, respectively, as well as the predominance of the age group of 15–17 years old 48 (69.6%) and 68 (75.6%) people in 2020 and 2021, respectively. In the structure of the methods concerning committing incomplete suicidal attempts, the administration of medications and other substances, as well as self-harm, were most commonly recorded. Conclusion: incomplete suicide attempts and the number of suicide deaths among children and adolescents of the Krasnodar Territory were analyzed by age and sex. The main ways of implementing auto-aggressive behavior, representation in various regions of the Krasnodar Territory, as well as the measures conducted by outpatient and inpatient psychiatric services in order to prevent suicidal behavior in the study cohort were identified. Keywords: suicidal activity, autoaggressive activity, completed suicide, suicidal attempt, children, adolescents. For citation: Boyko E.O., Vasyanina Yu.Sh., Mylnikova Yu.A., Aleksanyan E.K. Prevalence of suicidal behavior in children and adolescents of the Krasnodar Territory. Russian Journal of Woman and Child Health. 2022;5(3):223–227 (in Russ.). DOI: 10.32364/2618-8430-2022-5-3-223-227.